IRE Teachers Competence In Using Information and Communication Technology In Aceh Barat District - Sy. Rohana (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This study intends to examine the competence of Islamic religious education (IRE) teachers in Aceh Barat to utilize information and communication technology (ICT) in the classroom. This is a qualitative study employing the descriptive analysis method. Interviews and documentation are used to collect data. The study found that IRE teachers still lack competence in using ICT in the classroom, likely because they are used to using more traditional methods of instruction. In addition, IRE educators' familiarity with and comfort with ICT is restricted because they are not routinely used in their everyday work. The majority of instructional materials consist of slides and videos viewed through in focus. The absence of supporting facilities, such as in focus not being available in every classroom, hinders the use of information technology by IRE teachers. In addition, teachers have limited opportunity to participate in trainings. IRE teachers make efforts to inspire themselves by participating in school-based training and, if possible, studying with other teachers. The school wholeheartedly supports it despite the fact that not all teachers have the necessary facilities.